Wireless capsule endoscopy: a comparison with push enteroscopy in patients with gastroscopy and colonoscopy negative gastrointestinal bleeding - Mylonaki, M (Copyright 2003 by Gut, 2003)
Background: The development of wireless capsule endoscopy allows painless imaging of the small intestine. Its clinical use is not yet defined. The aim of this study was to compare the clinical efficacy and technical performance of capsule endoscopy and push enteroscopy in a series of 50 patients with colonoscopy and gastroscopy negative gastrointestinal bleeding. Methods: A wireless capsule endoscope was used containing a CMOS colour video imager, transmitter, and batteries. Approximately 50 000 transmitted images are received by eight abdominal aerials and stored on a portable solid state recorder, which is carried on a belt. Push enteroscopy was performed using a 240 cm Olympus video enteroscope. Results: Studies in 14 healthy volunteers gave information on normal anatomical appearances and preparation. In 50 patients with gastrointestinal bleeding and negative colonoscopy and gastroscopy, push enteroscopy was compared with capsule endoscopy. A bleeding source was discovered in the small intestine in 34 of 50 patients (68%). These included angiodysplasia (16), focal fresh bleeding (eight), apthous ulceration suggestive of Crohn’s disease (three), tumour (two), Meckel’s diverticulum (two), ileal ulcer (one), jejunitis (one), and ulcer due to intussusception (one). One additional intestinal diagnosis was made by enteroscopy. The yield of push enteroscopy in evaluating obscure bleeding was 32% (16/50). The capsule identified significantly more small intestinal bleeding sources than push enteroscopy (p<0.05). Patients preferred capsule endoscopy to push enteroscopy (p<0.001). Conclusions: In this study capsule endoscopy was superior to push enteroscopy in the diagnosis of recurrent bleeding in patients who had a negative gastroscopy and colonoscopy. It was safe and well tolerated.